An improved method to determine neutron fluence in high energy medical accelerators using activation detectors - Papadopoulos, K.; Siltzovalis, G.; Savva, M. I.; Vasilopoulou, T.; Georgolopoulou, P.; Karaiskos, P.; Kalef-Ezra, J.; Stamatelatos, I. E. (HNPS Advances in Nuclear Physics, 2019)
Scope of the present work was to test the hypothesis that a generic simulation geometry can adequately describe a high energy medical accelerator head for the purpose of estimating the parasitic neutron fluence levels at the position of the isocenter. The experiment was performed using an Elekta Synergy 18 MV linear accelerator. Gold, cobalt, indium and copper activation foils were used. Activation measurements were performed using a calibrated HPGe detector based spectrometry system. Four generic accelerator head models were considered. Neutron spectrum averaged cross-section data for each foil were derived for the examined configurations using the Monte Carlo code MCNP5 in conjuction with cross section data obtained from the International Reactor Dosimetry and Fusion File (IRDFF). It was concluded that the accelerator head can be adequately described either as a solid tungsten sphere of 10 cm radius or a spherical tungsten shell 20 cm in external diameter and 10 cm in thickness. This work contributes towards the development of a simple and computationally cost effective method for the determination of neutron fluence around high energy medical accelerators and therefore the optimization of the radiation protection of the patients and staff in radiation therapy.